International research management studies in interdisciplinary methods from business, government and academia - Birnbaum-More, Philip H.; Rossini, Frederick A.; Baldwin, Donald R. (Oxford University Press, 2011)
This book presents a group of papers that describe the preconditions, processes, and outcomes of interdisciplinary research projects from the United States, Canada, Israel, Japan, Brazil, the German Democratic Republic, and Romania. The papers describe the problems and approaches to successfully managing projects in government, private firms, and universities. The book also includes a comprehensive, annotated bibliography.